Concentration of biopetrol synthesized from palmitic acid through catalytic cracking using zeolite as catalyst - Mohd Addli, Suhaimi (2009)
Biofuel is defined as fuel produced from derivation of vegetable oils and specifically, biopetrol is defined as fuel which has the same characteristic with the petrol, but is produced from palmitic acid that is dominated in palm oil where the conversion of palmitic acid is done to get the molecular formula and structure of isooctane. Due to depletion of fossil fuel, environmental issues, and rising of petrol price, biopetrol can be the alternative fuel to the fossil fuel. Catalytic cracking method is conducted in this research due to the low yields from thermal cracking method. Futhermore, Malaysia is plenty with palm oil which palmitic acid is dominated in palm oil composition. In recent years, there have been several other studies on the production of hydrocarbons from palm oil mainly bio-gasoline (biopetrol) which have been carried out using cracking catalysts. Zeolites have shown excellent performance as solid acid cracking catalysts due to their higher selectivity. Many researcher have studied that catalytic cracking method will produce much higher yields than thermal cracking method. Through catalytic cracking process, palmitic acid is catalytic cracked with 4 different amount of catalyst – 1g, 5g, 10g, and 20g. The distillated product is diluted with 4 different dilution mixture solution – 1%, 5%, 10%, and 20%. All the product samples are analyzed with Gas Chromatographer (GC). The isooctane concentrations are increased when the amount of catalysts are increased, but not obviously. The lowest percentage concentration of isooctane obtained is 9.1822 % and the highest percentage concentration of isooctane obtained is 20.7210 %. These yields are much higher than the yields produced from thermal cracking method which is 3% to 5 %. It showed that the catalytic cracking method will produce much higher yields for biopetrol synthesized compared to thermal cracking method. This experiment should be conducted in dynamic state to optimize the yields.